Matematyka

Autorzy:Drążek Anna, Duvnjak Ewa, Kokiernak-Jurkiewicz Ewa

Wydawnictwo:WSiP

Rok wydania:2016

Wykonaj działania. a) (√6-√7)∙(√6+√7) 4.43 gwiazdek na podstawie 7 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Wykonaj działania. a) (√6-√7)∙(√6+√7)

1
 Zadanie
2
 Zadanie
3
 Zadanie

4
 Zadanie

5
 Zadanie
6
 Zadanie

Korzystamy ze wzorów skróconego mnożenia:

`(a-b)(a+b)=a^2-b^2`

`(a+b)^2=a^2+2ab+b^2` 

 

`a) \ \ (sqrt6-sqrt7)*(sqrt6+sqrt7)=(sqrt6)^2-(sqrt7)^2=6-7=-1`

`b) \ \ (3-sqrt5)*(3+sqrt5)=3^2-(sqrt5)^2=9-5=4`

`c) \ \ (3sqrt5+4)*(3sqrt5-4)=(3sqrt5)^2-4^2=9*5-16=45-16=29`

`d) \ \ (8-3sqrt7)*(8+3sqrt7)=8^2-(3sqrt7)^2=64-9*7=64-63=1`

`e) \ \ (4sqrt2-3sqrt8)*(3sqrt8-4sqrt2)=(-1)*(3sqrt8-4sqrt2)*(3sqrt8-4sqrt2)=`

`=(-1)*(3sqrt8-4sqrt2)^2=(-1)*((3sqrt8)^2-2*3sqrt8*4sqrt2+(4sqrt2)^2)=`

`=(-1)*(9*8-24sqrt(8*2)+16*2)=(-1)*(72-24sqrt16+32)=(-1)*(104-24*4)=`

`=(-1)*(104-96)=(-1)*8=-8`

`f) \ \ (3sqrt3+2sqrt27)*(3sqrt3+2sqrt27)=(3sqrt3+2sqrt27)^2=`

`=(3sqrt3)^2+2*3sqrt3*2sqrt27+(2sqrt27)^2=9*3+12sqrt(3*27)+4*27=`

`=27+12sqrt81+108=27+12*9+108=135+108=243`